Novel Rh(Pd)-Cu(Ni) supported catalysts for oxy-steam reforming of methanol - Pawel Mierczynski (Arabian Journal of Chemistry, 2020)
Monometallic copper, nickel and bimetallic Pd(Rh)-Cu(Ni) catalysts supported on a binary oxide containing various content of ZrO2 and Al2O3 were prepared by impregnation method. Their physicochemical and catalytic properties in oxy-steam reforming of methanol reaction (OSRM) were extensively investigated. Selecting an optimal composition of the catalyst for the OSRM process was the main goal of this work. The influence of zirconia content on the reactivity and physicochemical properties of supported copper catalysts in OSRM was also studied. The reactivity measurements showed that the supported copper catalyst was more active than the nickel catalyst. The catalytic measurements showed that the catalyst properties depend on their surface composition, acidity and adsorption properties. High selectivity of supported copper catalyst with composition 20%Cu/ZrO2·Al2O3 (Zr:Al = 1:2) towards carbon dioxide and hydrogen was confirmed. In addition, the promotion effect of palladium and rhodium on the activity of monometallic supported copper and nickel catalysts in OSRM was confirmed. The most active system in the OSRM process was 0.5%Rh-20%Cu/ZrO2·Al2O3. Keywords: Reforming of methanol, Copper catalyst, Binary oxide, Hydrogen production, Bimetallic catalysts